Cloning and sequence of the Salmonella typhimurium hemL gene and identification of the missing enzyme in hemL mutants as glutamate-1-semialdehyde aminotransferase. - Elliott, T (1990)
Salmonella typhimurium forms the heme precursor delta-aminolevulinic acid (ALA) exclusively from glutamate via the five-carbon pathway, which also occurs in plants and some bacteria including Escherichia coli, rather than by ALA synthase-catalyzed condensation of glycine and succinyl-coenzyme A, which occurs in yeasts, fungi, animal cells, and some bacteria including Bradyrhizobium japonicum and Rhodobacter capsulatus. ALA-auxotrophic hemL mutant S. typhimurium cells are deficient in glutamate-1-semialdehyde (GSA) aminotransferase, the enzyme that catalyzes the last step of ALA synthesis via the five-carbon pathway. hemL cells transformed with a plasmid containing the S. typhimurium hemL gene did not require ALA for growth and had GSA aminotransferase activity. Growth in the presence of ALA did not appreciably affect the level of extractable GSA aminotransferase activity in wild-type cells or in hemL cells transformed with the hemL plasmid. These results indicate that GSA aminotransferase activity is required for in vivo ALA biosynthesis from glutamate. In contrast, extracts of both wild-type and hemL cells had gamma,delta-dioxovalerate aminotransferase activity, which indicates that this reaction is not catalyzed by GSA aminotransferase and that the enzyme is not encoded by the hemL gene. The S. typhimurium hemL gene was sequenced and determined to contain an open reading frame of 426 codons encoding a 45.3-kDa polypeptide. The sequence of the hemL gene bears no recognizable similarity to the hemA gene of S. typhimurium or E. coli, which encodes glutamyl-tRNA reductase, or to the hemA genes of B. japonicum or R. capsulatus, which encode ALA synthase. The predicted hemL gene product does show greater than 50% identity to barley GSA aminotransferase over its entire length. Sequence similarity to other aminotransferases was also detected.